2018
DOI: 10.1093/nar/gky823
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into histone deposition and nucleosome assembly by the chromatin assembly factor-1

Abstract: Eukaryotic chromatin is a highly dynamic structure with essential roles in virtually all DNA-dependent cellular processes. Nucleosomes are a barrier to DNA access, and during DNA replication, they are disassembled ahead of the replication machinery (the replisome) and reassembled following its passage. The Histone chaperone Chromatin Assembly Factor-1 (CAF-1) interacts with the replisome and deposits H3–H4 directly onto newly synthesized DNA. Therefore, CAF-1 is important for the establishment and propagation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 121 publications
5
59
0
Order By: Relevance
“…2D). These results highlight the importance of Cac1 for replisome and G2/M progression and are in good agreement with a previous study showing that Cac1 is essential for the Caf1 protein complex assembly and H3/H4 binding [13,26].Previous studies have revealed the contribution of the Caf1 subunits for H3/H4 assembly and nucleosome deposition under DNA stress conditions [30][31][32]. To further investigate the effect of cac2-or cac3-deletion on DNA replication under these conditions, we incubated the Caf1 mutant strains with 20 mM HU and measured their replication times as described above.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…2D). These results highlight the importance of Cac1 for replisome and G2/M progression and are in good agreement with a previous study showing that Cac1 is essential for the Caf1 protein complex assembly and H3/H4 binding [13,26].Previous studies have revealed the contribution of the Caf1 subunits for H3/H4 assembly and nucleosome deposition under DNA stress conditions [30][31][32]. To further investigate the effect of cac2-or cac3-deletion on DNA replication under these conditions, we incubated the Caf1 mutant strains with 20 mM HU and measured their replication times as described above.…”
supporting
confidence: 93%
“…Histone chaperones are essential for the process of DNA replication-coupled (RC) nucleosome deposition by facilitating correct histone assembly, post-translational modifications and localization during DNA replication [5][6][7][8].Newly synthesized histones are assembled into nucleosomes by several histone chaperones including Asf1, Rtt109, Rtt106, Caf1 and the FACT complex that act in a sequential and coordinated manner to facilitate nucleosome deposition during DNA replication [5,[9][10][11]. In budding yeast, Asf1 binds newly synthesized H3-H4 histones and promotes H3K56 acetylation by Rtt109 [12].Acetylation of H3K56 enhances H3-H4 binding to Caf1 and Rtt106 that deposit (H3/H4) 2 tetramers directly onto the DNA [13][14][15]. Previous studies have shown that single-or double-mutations of histone chaperone genes including Caf1 subunits, RTT106, ASF1 or RTT109 can lead to severe replication stress, checkpoint activation, increased recombination and sensitivity to DNA damaging agents [14,16,17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitant with DNA replication, PCNA also controls chromatinization of the newly synthesized DNA by recruiting the chromatin assembly factor CAF-1 and other histone chaperone complexes (Alabert et al, 2017;Sauer et al, 2018). In general, these interactions are mediated by a conserved motif termed PCNA-interacting peptide (PIP)box present on most PCNA binding partners (Choe and Moldovan, 2017;Mailand et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…tNASP, Hsp90, Hsc70, and histone H4 elute in these fractions. Another complex composed of sNASP, HAT1, H3 and H4 elutes with a molecular weight of about 100 kDa (fractions [30][31][32]. Remarkably, in siJMJD1B derived cytosolic extracts, the complex composed of tNASP, Hsp90, Hsc70, histones H3 and H4 is shifted to a heavier molecular size fraction, comprising fractions 22-24, of about 600 kDa (Fig.…”
Section: Sijmjd1b Cells Accumulate Histones H3 and H4 At Early Steps mentioning
confidence: 90%